Designs for Measurement of Status - Wark, David M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
An examination of typical situations concerning the status of a variable is followed by a discussion of the measurement and empirical problems involved in measuring current status. Arguments for more consideration of variability, particularly individual variation, are presented. Among the problems discussed are (1) describing large samples through randomized and controlled sampling, (2) screening subjects into special categories for some special programs, (3) diagnosing an individual's abilities in different skills, (4) establishing a basis for measuring and describing behavioral change, (5) determining the validity and reliability of instruments used and of individuals tested, and (6) solving empirical problems of motivation, practice effect of multiple testing, disruptive effects on test results, and of the time involved. References are given. (NS)
ERIC Note: Paper presented at International Reading Association conference, Boston, Mass., April 24-27, 1968.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Research; Instrumentation; Research Design; Research Methodology; Measurement Instruments; Research Problems; Sampling; Test Reliability; Test Validity